Electrodiagnostic Findings in a Case of Pyle’s Disease: A Case-Report - Behroozinia, Maryam; Khosrawi, Saeid (Iranian Journal of Child Neurology, 2025)
Pyle’s disease (PD), also known as metaphyseal dysplasia, is a rare genetic skeletal disorder characterized by a specific radiologic feature known as the Erlenmeyer-flask deformity, the expansion of trabecular metaphyses, specifically in the distal aspects of long bones. The main pathophysiology of this disease is caused by mutations in the Secreted Frizzled-Related Protein 4 (SFRP4) gene. This case report aims to discuss the electrodiagnostic findings of an 8-year-old girl diagnosed with PD. This evaluation revealed normal sensory nerve action potentials (SNAP); however, compound muscle action potentials (CMAP) showed minimal amplitudes with increased latencies and profound reductions in nerve conduction velocities (NCVs), particularly in the lower limbs. These features are consistent with peripheral motor polyneuropathy with a mixed axonal and demyelinating pattern. This case is reported because PD is an uncommon disorder, and until now, there has been no literature describing the electrodiagnostic features of this disease.